FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN PENGISIAN EARLY WARNING SCORE (EWS) SAAT TRANSFER PASIEN DI INSTALASI GAWAT DARURAT - Muhammad Irwan; Happy Yulan Three (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The accuracy of Early Warning Score (EWS) is a crucial factor in the early detection of patient deterioration in the Emergency Department (ED). This study aims to analyze the relationship between nurses' knowledge, workload, training, head nurse supervision, and patient safety culture on the accuracy of EWS documentation at Aulia Hospital Pekanbaru. A quantitative cross-sectional design was used. The sample consisted of 30 ED nurses, selected using total sampling. Data were collected using a questionnaire and analyzed through univariate and bivariate analysis with chi-square tests. The results showed that the majority of respondents had good knowledge (40%), reported high workload (63.3%), had participated in training (83.3%), received good head nurse supervision (56.7%), and reported good patient safety culture (74.3%). The accuracy of EWS documentation was mostly categorized as accurate (50%). Bivariate analysis revealed significant relationships between knowledge (p=0.035), workload (p=0.021), training (p=0.039), supervision (p=0.036), and patient safety culture (p=0.039) with EWS documentation accuracy. It is recommended that hospital management improve training, supervision, and workload management to support patient safety.Keywords: Early Warning Score, Documentation Accuracy, Nurses' Knowledge, Workload, Patient Safety Culture